Dampak Ekstrakulikuler Basket terhadap Kesehatan Fisik dan Mental siswa SMAN 1 Balung: Dampak Ekstrakulikuler Basket terhadap Kesehatan Fisik dan Mental siswa SMAN 1 Balung - Afiffuddin, Muhammad; Hardovi, Bahtiar Hari; Apriliyanto, Rizky (Jurnal Porkes, 2025)
This study aims to determine the impact of extracurricular basketball on the physical and mental health of students of SMAN 1 Balung. The method used was descriptive quantitative with purposive sampling technique, involving 20 students who actively participated in extracurricular basketball. Data were collected through a questionnaire questionnaire containing 12 statements divided into two categories: physical health (P1-P6) and mental health (P7-P12). The results showed that the total respondents who answered from 12 items of the questionnaire questionnaire there were 3 answers that disagreed with the statement (P), namely P3, P6, and P7, this indicates that students who take part in extracurricular basketball still partly disagree, especially in P3 with a percentage level of 25% and for all statements (P1-P12) the answers agree and strongly agree all answered with different percentage levels. For answers agreeing to category P6 puts the top with a percentage (91.66%) and for answers strongly agreeing to category P4 with a percentage (91.66%). In categories P1, P2, P9, and P10 have the same percentage for answers strongly agree with a percentage (58.33%) and answers agree with a percentage (66.66%) and no respondents answered disagree. It is concluded that this extracurricular activity has a positive impact on students' physical and mental health.